Aberrant Gene Expression Profiling in Men With Sertoli Cell-Only Syndrome - Chen, Tong; Wang, Yichun; Tian, Linlin; Guo, Xuejiang; Xia, Jiadong; Wang, Zengjun; Song, Ninghong (Frontiers in Immunology, 2022)
Sertoli cell-only syndrome (SCOS) is the most severe and common pathological type of non-obstructive azoospermia. The etiology of SCOS remains largely unknown to date despite of a handful of studies reported in this area. According to the gene expression of testicular tissue samples in six datasets from the Gene Expression Omnibus, we detected 1441 differentially expressed genes (DEGs) between SCOS and obstructive azoospermia (OA) testicular tissue samples. Enriched GO terms and KEGG pathways for the downregulated genes included various terms and pathways related to cell cycle and reproduction, while the enrichment for the upregulated genes yielded many inflammation-related terms and pathways. In accordance with protein-protein interaction (PPI) network, all genes in the most critical module belonged to the downregulated DEGs, and we obtained nine hub genes, including CCNB1, AURKA, CCNA2, BIRC5, TYMS, UBE2C, CDC20, TOP2A, and OIP5. Among these hub genes, six were also found in the most significant SCOS-specific module obtained from consensus module analysis. In addition, most of SCOS-specific modules did not have a consensus counterpart. Based on the downregulated genes, transcription factors (TFs) and kinases within the upstream regulatory network were predicted. Then, we compared the difference in infiltrating levels of immune cells between OA and SCOS samples, and found a significantly higher degree of infiltration for the majority of immune cells in SCOS than OA samples. Moreover, CD56bright natural killer cell was significantly associated with six hub genes. Enriched hallmark pathways in SCOS had remarkably more upregulated pathways than the downregulated ones. Collectively, we detected DEGs, significant modules, hub genes, upstream TFs and kinases, enriched downstream pathways, and infiltrated immune cells that might be specifically implicated in the pathogenesis of SCOS. These findings provide new insights into the pathogenesis of SCOS and fuel future advances in its theranostics.